Dynamics of elastically connected double-functionally graded beam systems with different boundary conditions under action of a moving harmonic load - Simsek, Mesut; Cansiz, Sinan (ELSEVIER SCI LTD, 2012)
This paper studies the dynamic responses of an elastically connected double-functionally graded beam system (DFGBS) carrying a moving harmonic load at a constant speed by using Euler-Bernoulli beam theory. The two functionally graded (FG) beams are parallel and connected with each other continuously by elastic springs. Six elastically connected double-functionally graded beam systems (DFGBSs) having different boundary conditions are considered. The point constraints in the form of supports are assumed to be linear springs of large stiffness. It is assumed that the material properties follow a power-law variation through the thickness direction of the beams. The equations of motion are derived with the aid of Lagrange's equations. The unknown functions denoting the transverse deflections of DFGBS are expressed in polynomial form. Newmark method is employed to find the dynamic responses of DFGBS subjected to a concentrated moving harmonic load. The influences of the different material distribution, velocity of the moving harmonic load, forcing frequency, the rigidity of the elastic layer between the FG beams and the boundary conditions on the dynamic responses are discussed. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Vibration; Beam; Functionally graded beam; Elastically connected double-beam system; Moving harmonic load; FORCED TRANSVERSE VIBRATIONS; PRESTRESSED DAMPED BEAM; TIMOSHENKO BEAM; STATIC ANALYSIS; FINITE-ELEMENT; NONLINEAR VIBRATION; BEHAVIOR; Mechanics; Materials Science